2016
DOI: 10.1097/01.prs.0000475775.44891.56
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Utility Assessment of Mesh Selection in Clean-Contaminated Ventral Hernia Repair

Abstract: This cost-utility analysis suggests that synthetic mesh repair of clean-contaminated hernia defects is more cost-effective than acellular dermal matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Available evidence is somewhat conflicting with several studies identifying increased costs associated with the use of biological grafts [29,30]. Conversely, more recent literature has identified no significant cost increase associated with the use of biological grafts when assessing use in infected wounds [31] or departmental revenue [32]. Accordingly, Huerta et al concluded that there exists no high-quality clinical trial to demonstrate the costbenefits of biological materials [27].…”
Section: Discussionmentioning
confidence: 95%
“…Available evidence is somewhat conflicting with several studies identifying increased costs associated with the use of biological grafts [29,30]. Conversely, more recent literature has identified no significant cost increase associated with the use of biological grafts when assessing use in infected wounds [31] or departmental revenue [32]. Accordingly, Huerta et al concluded that there exists no high-quality clinical trial to demonstrate the costbenefits of biological materials [27].…”
Section: Discussionmentioning
confidence: 95%
“…A cost-utility analysis is commonly used to determine the cost of particular interventions in terms of their utility, which includes quantity needed over a lifetime as well as quality of life. It has been used in a variety of surgical studies to date and have helped inform surgeon decisions Chatterjee et al, 2014;Fischer et al, 2016;Krishnan et al, 2016;Krishnan et al, 2015;Krishnan et al, 2014;Offodile et al, 2015;Thoma et al, 2012;Sheckter et al, 2018). Such a technique allows for identification of interventions with the best clinical outcomes and best value, which is especially important with the large healthcare costs associated with breast oncology management (Lang et al, 2014;Bekelman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…24 The main disadvantage of these biologic implants is their significantly higher cost compared with synthetic mesh. 38 As a result, surgeons are often faced with deciding between higher wound complications or higher costs in dirty and contaminated wounds. With new innovations in biosynthetic meshes, which appear to have similar anti-infection properties as biologic meshes at a reduced cost, studies such as the Contaminated Ventral Hernia Repair Using Biosynthetic Absorbable Mesh (COBRA) trial are showing comparable recurrence rates to synthetic mesh with improved quality of life; however, long-term outcomes and cost-effectiveness still need to be assessed.…”
Section: Component Separationmentioning
confidence: 99%